1993
DOI: 10.1007/bf01516936
|View full text |Cite
|
Sign up to set email alerts
|

Locoregional therapy with polyethylene-glycol-modified interleukin-2 of an intradermally growing hepatocellular carcinoma in the guinea pig induces T-cell-mediated antitumor activity

Abstract: Therapy with repeated intratumoral and perilymphatic administration of relatively low doses of polyethylene-glycol(PEG)-modified interleukin-2 (IL-2) in the syngeneic guinea pig line 10 (L10) hepatocarcinoma results in significant local tumor growth inhibition and a delay in development of regional lymph node metastases of more than 3 weeks when compared to controls. Occasionally animals are cured of tumor. The mechanism of this antitumor activity was studied. The antitumor activity of locoregionally administe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Recent studies have focused on the use of cytokines to enhance the immune system in an attempt to decrease tumor growth (8,9,24). Systemic administration of cytokines is accompanied by unwanted serious side effects (5, 7).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have focused on the use of cytokines to enhance the immune system in an attempt to decrease tumor growth (8,9,24). Systemic administration of cytokines is accompanied by unwanted serious side effects (5, 7).…”
Section: Discussionmentioning
confidence: 99%
“…Nearly all patients treated with IL‐2 experience side effects,10–12 which can be severe and even life threatening. Studies have demonstrated that low‐dose delivery of IL‐2 reduces the incidence and severity of the life‐threatening side effects seen with high‐dose systemic delivery 13–18. Consequently, a method that would allow continuous low‐dose delivery of IL‐2 without tethering the patient to an infusion system or requiring hospitalization would be desirable.…”
Section: Introductionmentioning
confidence: 99%
“…In the chemotherapy of a localized tumor in the liver, direct drug injection to the liver has been suggested to enhance local drug distribution (Mattijssen et al 1992;Dubinett et al 1993;Balemans et al 1993).…”
mentioning
confidence: 99%